2023
DOI: 10.1007/s00705-022-05666-6
|View full text |Cite
|
Sign up to set email alerts
|

Molecular characterisation and tracking of severe acute respiratory syndrome coronavirus 2 in Thailand, 2020–2022

Abstract: The global COVID-19 pandemic, caused by the novel severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2), was first detected in China in December 2019. To date, there have been approximately 3.4 million reported cases of COVID-19 and over 24,000 deaths in Thailand. In this study, we investigated the molecular characteristics and evolution of SARS-CoV-2 in Thailand from 2020 to 2022. Two hundred sixty-eight SARS-CoV-2 isolates, collected mostly in Bangkok from COVID-19 patients, were characterised by part… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
32
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 31 publications
(36 citation statements)
references
References 29 publications
4
32
0
Order By: Relevance
“…The vertical dotted lines indicate the quarter, and the number above the bar graph indicates infection-induced seropositivity estimated for each quarter. Color shaded areas indicate the number of nasopharyngeal swab samples that tested positive (right Y axis) and subsequently identified the SARS-CoV-2 variants (n = 7,729) that was obtained from our previous study [ 7 ]. Data on SARS-CoV-2 variants were identified using sequencing and multiplex real-time reverse transcription polymerase chain reaction (RT-PCR) to depict the predominant wave for individual SARS-CoV-2 variants in Thailand.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The vertical dotted lines indicate the quarter, and the number above the bar graph indicates infection-induced seropositivity estimated for each quarter. Color shaded areas indicate the number of nasopharyngeal swab samples that tested positive (right Y axis) and subsequently identified the SARS-CoV-2 variants (n = 7,729) that was obtained from our previous study [ 7 ]. Data on SARS-CoV-2 variants were identified using sequencing and multiplex real-time reverse transcription polymerase chain reaction (RT-PCR) to depict the predominant wave for individual SARS-CoV-2 variants in Thailand.…”
Section: Resultsmentioning
confidence: 99%
“…The omicron variant was first detected in Thailand in mid-December 2021. The incidence of omicron infection rapidly increased and subsequently became the predominant variant by January 2022 [ 7 ]. A study demonstrated that the omicron variant was highly transmissible and can evade the immune system even in vaccinated or previously infected individuals [ 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…The outbreaks were most intense in the Bangkok Metropolitan Region (BMR) – an inter-connected and densely populated area of the country, comprising the capital city of Thailand, Bangkok, and five surrounding provinces, Nakhon Pathom, Nonthaburi, Pathum Thani, Samut Prakan and Samut Sakhon. While molecular evolution of SARS-CoV-2 circulating in Thailand in 2020–2022 has already been previously described [3, 4], a comprehensive spatiotemporal analysis of the virus is still lacking.…”
Section: Introductionmentioning
confidence: 99%
“…Time course of the first infection (circle) and reinfection (square) were plotted versus the sequencing data of the SARS-CoV-2 predominant variant obtained in our previous study [5]. …”
Section: Resultsmentioning
confidence: 99%
“…The timing of the infection was used to assign the pre-Omicron or Omicron infection period. According to the sequenced surveillance data for the predominant SARS-CoV-2 variant obtained in our previous study in Thailand [5], infections that occurred before January 2022 were considered from the pre-Omicron infection period.…”
Section: Methodsmentioning
confidence: 99%